2020
DOI: 10.35333/jrp.2020.249
|View full text |Cite
|
Sign up to set email alerts
|

Nepeta humilis Bentham: First evaluation of phenolic profile and radical scavenging potential

Abstract: In traditional medicine, Lamiaceae plants are widely used as a cure for various health problems. Nepeta humilis is one of the Lamiaceae plants of Iranian-Turkish district growing naturally in the South East Anatolia. The present study was designed to investigate the radical scavenging activity and total phenolic content of Nepeta humilis as well as to determine the phenolic constituents of the extracts of flowers, leaves and roots using a previously validated RP-HPLC-DAD method for the first time. The total ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…In addition, the concentration of the different components in the methanol and water extracts might be different, and this was not specified in our data. In accordance with our results, the presence of flavones and hydroxycinnamic acid in the members of the Nepeta genus was reported in earlier studies [23][24][25][26][27].…”
Section: Resultssupporting
confidence: 94%
“…In addition, the concentration of the different components in the methanol and water extracts might be different, and this was not specified in our data. In accordance with our results, the presence of flavones and hydroxycinnamic acid in the members of the Nepeta genus was reported in earlier studies [23][24][25][26][27].…”
Section: Resultssupporting
confidence: 94%
“…Similarly, an investigation about analysis of N. humilis extracts with RP-HPLC-DAD showed that the major component in all parts of the plant, especially in flowers, is rosmarinic acid, while flowers contain phenolic compounds such as chlorogenic acid, luteolin and apigenin [ 38 ].…”
Section: Resultsmentioning
confidence: 99%
“…It is a member of the tribe Mentheae (subfamily Nepetoideae) and includes about 300 species (Asgarpanah et al, 2014). In Turkey, there are 40 taxa in the Nepeta genus, 16 of which are endemic (Gökbulut & Yılmaz, 2020). Nepeta species are commonly utilized in traditional medicine by the local people, primarily as spasmolytic, diuretic and bronchodilator agents (Sharma et al, 2021).…”
Section: Introductionmentioning
confidence: 99%